Channel Correlation-Based Adaptive Power Transmission for Free-Space Optical Communications - Bai-Shan Zhao; Peng-Fei Lv; Yan-Qing Hong (Photonics)
Free-space optical (FSO) communication has received widespread attention as a high-bandwidth, low-latency communication technique. However, the scintillation effect caused by atmospheric turbulence leads to intensity fluctuations of the transmission signal, which, in turn, affects the performance of the FSO communication system. This paper proposes a channel correlation-based adaptive power transmission for FSO communications. Based on the correlation between uplink and downlink turbulence channels, the power of the reverse transmission signal is adjusted by the fluctuation strength of the received uplink or downlink transmission signal and the channel correlation coefficient to improve the system’s performance. The proposed technique is investigated through a simulation using established uplink and downlink channels with different link distances and turbulence intensities. The simulation results show that the bit error rate (BER) performance of the proposed technique is significantly improved compared to the fixed threshold decision (FTD) technique, and it is close to the adaptive threshold decision (ATD) technique. The proposed technique provides an effective optimization scheme for FSO communications.